Comparison of vaccine hesitancy during the low and high points of COVID-19 in a population under international sanctions: A longitudinal mixed-methods study in Iran - Khankeh, Hamidreza; Pourebrahimi, Mohammad; Hosseinabadi-Farahani, Mohammadjavad; Farrokhi, Mehrdad; Khanjani, Mohammad Saeed; Shojafard, Javad; Hamedanchi, Arya; Ranjbar, Maryam; Jenabi Ghods, Mariye; Ahmadi, Shokoufeh; Ghanaatpisheh, Elham; Saatchi, Mohammad (Frontiers in Public Health, 2023)
Introduction Along with the challenges of COVID-19 vaccine supply in low-income countries, vaccine hesitancy was another problem for the health system. The aim of this study was to deeply understand the challenges of vaccine acceptance, the vaccination process, and to compare the affecting vaccine acceptance in the high and low points of the epidemic in Iran. Methods In the qualitative part of this mixed-methods study, content analysis was used to investigate experiences and perceptions about COVID-19 vaccination in four groups. In the quantitative study, in March 2021 (low point), and on August 1, 2021 (high point), two population-based cross-sectional studies were performed in Tehran and its rural, with sample sizes of 1,200 and 1,872 people aged over 18 years, respectively. Multinomial (polytomous) logistic regression was used to determine the factors affecting hesitation and unwillingness to receive the vaccine. Results Disbelief in vaccine safety, vaccine distrust, ignorance and confusion, and inadequate facilities were the common reasons extracted in the two qualitative studies. At the low and high points of the epidemic, vaccine acceptance was 83.6% (95% CI: 81.3–85.9) and 65.8% (95% CI: 65.8–71.0), respectively. Residence in rural areas, (Odds Ratio: 0.44, p = 0.001), being a student (Odds Ratio: 0.41, p = 0.011), housewives (Odds Ratio: 0.63, p = 0.033), illiteracy (Odds Ratio: 4.44, p = 0.001), and having an underlying disease (Odds Ratio: 4.44, p = 0.001) were factors affecting on vaccine acceptance. Discussion Counter-intuitively, acceptance did not increase at the peak of epidemic. The presence of obstacles, such as increased distrust in the effectiveness of vaccines due to the occurrence of multiple peaks in different vaccinated countries, as well as the influence of the media, anti-vaccine campaigns, and lack of proper communication about risks caused more hesitation. More investigation to understand how people accept or reject vaccine and its long term consequences is recommended.